The engines of Hippocrates : from the dawn of medicine to medical and pharmaceutical informatics - Robson, Barry (John Wiley & Sons, 2009)
A unique, integrative look at information-based medicine. The convergence of medical science, biology, pharmacology, biomedical engineering, healthcare, and information technology is revolutionizing medical and scientific practice, and has broader social implications still being understood. The Engines of Hippocrates provides a unique, integrative, and holistic look at the new paradigm of information-based medicine, covering a broad range of topics for a wide readership. The authors take a comprehensive approach, examining the prehistory, history, and future of medicine and medical technology.